Implications of NKG2A in immunity and immune-mediated diseases - Wang, Xiaotong; Xiong, Huabao; Ning, Zhaochen (Frontiers in Immunology, 2022)
In recent studies, NKG2A is revealed to be a key immune checkpoint for both natural killer (NK) cells and CD8+ T cells. It form heterodimer receptors with CD94, and targets the peptide-presenting human leukocyte antigen-E (HLA-E) molecules. Upon crosslinking, NKG2A/CD94 delivers inhibitory signals for NK cells and CD8+ T cells, while blocking NKG2A can effectively unleash functions of these cytotoxic lymphocytes. The interaction between NKG2A and HLA-E contributes to tumor immune escape, and NKG2A-mediated mechanisms are currently being exploited to develop potential antitumor therapeutic strategies. In addition, growing evidence shows that NKG2A also plays important roles in other immune-related diseases including viral infections, autoimmune diseases, inflammatory diseases, parasite infections and transplant rejection. Therefore, the current work focuses on describing the effect of NKG2A on immune regulation and exploring its potential role in immune-mediated disorders.